Improving Writing Skills and Emotional Expression Through Diaries (Case Study in Grade V of SD Negeri 31 Jati Tanah Tinggi) - Noviani Herdianti; Hendrizal Hendrizal; Weni Yulastri (Journal of Educational Sciences, 2026)
This research is motivated by the low writing ability of students and the limited learning media that support cognitive and emotional aspects. The study aims to describe the process of diary writing in improving the ability to write experiences, changes in students' emotional expression after using diary media, and its impact on the learning process. The study used a qualitative approach with a case study type involving 20 students of class VC of SD Negeri 31 Jati Tanah Tinggi . The implementation of diary writing was carried out routinely for three months . Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman interactive analysis model. The research findings indicate that regular diary writing enhances students' writing skills by fostering idea development, vocabulary enrichment, sentence construction, and improved coherence, as well as enabling a more systematic organization of experiences. Furthermore, the use of a diary encourages positive emotional expression by boosting self-confidence, openness, self-reflection, and emotional awareness. These changes also enhanced learning participation, motivation, and positive social interaction, while creating a more conducive classroom atmosphere. Thus, the diary medium is effective for improving experience-based writing skills and supporting students' socio-emotional development during Indonesian language lessons in primary school.